IDENTIFIKASI DAGING SEGAR MENGGUNAKAN SENSOR WARNA RGB TCS3200-DB - Pambudi, Prastyono Eko; Sutanta, Edhy; -, Mujiman (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2014)
The high demand and limited availability of meat meat on the market, making the price of meat to be expensive, and more and more traders are mixing meat rotten meat into fresh meat. To avoid the risk, the public as consumers must beware and know the characteristics of rotten meat and the difference with the fresh meat. This research developed a tool detection fresh meat using RGB color sensor TCS3200-DB. Instrument works by measuring the composition of the RGB color in meat is identified and compared with the composition of the reference RGB color of fresh meat. The study begins by taking the composition of the RGB color of fresh meat samples as reference. RGB color composition is then recorded in the main program listing in the microcontroller. The instrument works by comparing the RGB color composition in meat detected by the reference RGB color composition. The microcontroller will determine the power of RGB color values ​​identified meat and then display it via an LCD. The results of this study indicate that fresh meat, G and B values ​​are closer to each other, respectively 3-38 and 3-29 to 4-27 and 4-25 G and for B the only difference being the value of R, which is the largest value of R is 58.